Medication analysis and pharmaceutical care for a child with Kawasaki disease: A case report and review of the literature. Issue 1 (6th January 2023) - Lai, Yingqiang; Feng, Meirou; Deng, Jianrong; Tan, Benren; Ban, Junfeng; Zheng, Jinkun
Abstract : Objective: To explore the ideas and methods of clinical pharmacists regarding drug therapy for children with Kawasaki disease. Methods: By participating in a whole drug treatment process for a child with Kawasaki disease, the rationality of the drug treatment plan was analyzed, pharmaceutical care was provided for the child, and a pharmaceutical care model suited to this child was developed. Results: After treatment, the child was discharged from the hospital, and all signs and major inflammatory indicators returned to normal. The child's parents were instructed to bring medication, visit regularly, and adjust medication. Conclusion: Through the entire process of pharmaceutical care, clinical pharmacists are able to identify and resolve drug treatment-related issues in a timely manner, and also make suggestions on rational drug use, which can improve the safety and compliance of drug use in children and the quality of clinical drug treatment.